2022
DOI: 10.31539/josing.v3i1.4863
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Problem Focused Coping on Anxiety and Stress of Nursing Students During Online Learning

Abstract: This study aims to determine the effect of problem-focused coping on nursing students' anxiety and stress during online learning. This research method uses a quasi-experimental method with a pretest-posttest design with a control group. The results showed that most of the experimental group's initial anxiety was moderate (35.5%) and the control group was also moderate (35.5%). Most of the anxiety in the experimental group is normal and mild (29.0%) and the control group is moderate (41.9%). Most of the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Furthermore, Postma and White (2015), revealed that the four-component instructional design model provides conditions for measuring cognitive feedback considering the content and the development of the learner’s cognitive strategies, and finally, it is recommended that the model of four-component design should be considered a basis for teaching and learning in the classroom to develop abilities in clinical reasoning among dental students and in medical education (Postma & White, 2015). Yusup and Musharyanti (2022), aimed to compare the knowledge and skills in medication safety of nursing students after the medication-safety training using the 4C/ID. Training in medication safety using the 4C/ID approach could improve the medication-safety knowledge and skills of the nursing students.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Postma and White (2015), revealed that the four-component instructional design model provides conditions for measuring cognitive feedback considering the content and the development of the learner’s cognitive strategies, and finally, it is recommended that the model of four-component design should be considered a basis for teaching and learning in the classroom to develop abilities in clinical reasoning among dental students and in medical education (Postma & White, 2015). Yusup and Musharyanti (2022), aimed to compare the knowledge and skills in medication safety of nursing students after the medication-safety training using the 4C/ID. Training in medication safety using the 4C/ID approach could improve the medication-safety knowledge and skills of the nursing students.…”
Section: Introductionmentioning
confidence: 99%